ISU DASAR NEGARA INDONESIA MENJELANG PEMILU 1955: STUDI KASUS PIDATO POLITIK SOEKARNO DI AMUNTAI 27 JANUARI 1953 - Iqbal, Muhammad (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
"Islamic State versus National State" was a heated political issue throughout the 1950s that created highly tense and dividing debates among Indonesia's political communities. President Soekarno, a leading proponent of National State, raised this issue for the first time in his speech in Amuntai on January 27th, 1953. The present paper contends that this speech was crucial for the political discourse contestations that followed between the religiously-neutral Nasionalist camp and the Islamic camp. The former argued against the latter's idea of building an Islamic state in Indonesia and proposed instead, a secular state that guarantees the right of its citizens to observe their religious teachings. The value of Soekarno's speech could be seen from reactions it generated from the supporters of Islamic State who called it a smear campaign and a doctrine dangerous to their struggle to erect an Islamic state in Indonesia.